2020
DOI: 10.1117/1.nph.7.1.015012
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted functional brain connectivity networks in children with attention-deficit/hyperactivity disorder: evidence from resting-state functional near-infrared spectroscopy

Abstract: Significance: Attention-deficit/hyperactivity disorder (ADHD) is the most common psychological disease in childhood. Currently, widely used neuroimaging techniques require complete body confinement and motionlessness and thus are extremely hard for brain scanning of ADHD children. Aim: We present resting-state functional near-infrared spectroscopy (fNIRS) as an imaging technique to record spontaneous brain activity in children with ADHD. Approach: The brain functional connectivity was calculated, and the graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 73 publications
5
38
0
Order By: Relevance
“…For example, reduced gray matter volume in the right middle occipital gyrus ( Wang L. J. et al, 2020 ) and hyper-activation of occipital lobe function was found in ADHD ( Tian et al, 2008 ; Icer et al, 2019 ), indicating that atypical visual processing may play a key role. Previous study also reported that the decreased connectivity between the frontal cortex and visual cortex was associated with increased severity in ADHD symptoms ( Wang M. et al, 2020 ). Meanwhile, the interaction between the dorsal attention network and visual cortex is important for maintaining attention ( Shulman et al, 2009 ).…”
Section: Discussionmentioning
confidence: 77%
“…For example, reduced gray matter volume in the right middle occipital gyrus ( Wang L. J. et al, 2020 ) and hyper-activation of occipital lobe function was found in ADHD ( Tian et al, 2008 ; Icer et al, 2019 ), indicating that atypical visual processing may play a key role. Previous study also reported that the decreased connectivity between the frontal cortex and visual cortex was associated with increased severity in ADHD symptoms ( Wang M. et al, 2020 ). Meanwhile, the interaction between the dorsal attention network and visual cortex is important for maintaining attention ( Shulman et al, 2009 ).…”
Section: Discussionmentioning
confidence: 77%
“…GE has been proposed and shown to be a robust and reliable biomarker in many fNIRS studies. 21 , 64 69 In most cases resting fNIRS data were used to calculate the FC matrices. GE values were always computed after a threshold value was adapted.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that disruptions in functional connectivity and topological network organization underlie various neurological disorders (Suo et al, 2015;Wang et al, 2020). Meanwhile, resting-state fNIRS has been widely used to capture network dysfunctions in the early stage and to aid diagnosis of many pediatric neurological conditions.…”
Section: Brain Connectome In Children With Neurological Disordersmentioning
confidence: 99%